Pollution Charges, Community Pressure, and Abatement Cost of Industrial Pollution in China - Wang, Hua (World Bank, Washington, DC, 2015)
The author evaluates the strength of the effect that community pressure and pollution charges have on industrial pollution control in China, and estimates the marginal cost of pollution abatement. He examines a well-documented set of plant-level data, combined with community-level data, to assess the impact of pollution charges and community pressure on industrial behavior in China. He constructs and estimates an industrial organic water pollution discharge model for plants that violate standards for pollution discharge, pay pollution charges, and are constantly under community pressure to further abate pollution. He creates a model and estimates implicit prices for pollution discharges from community pressure, which are determined jointly by the explicit price, the pollution levy. He finds that the implicit discharge price is at least as high as the explicit price. In other words, community pressure not only exists, but may be as strong an incentive as the pollution charge is for industrial firms to control pollution in China. The author's modeling approach also provides a way to estimate the marginal cost of pollution abatement. The empirical results show that the current marginal cost of abatement is about twice the effective charge rate in China.